Influence of biodiesel blending on physicochemical properties and importance of mathematical model for predicting the properties of biodiesel blend - Wakil, M.A.; Kalam, Md. Abul; Masjuki, Haji Hassan; Atabani, A.E.; Fattah, I.M.R. (Elsevier, 2015)
The growing demand for green world serves as one of the most significant challenges of modernization. Requirements like largest usage of energy for modern society as well as demand for friendly milieu create a deep concern in field of research. Biofuels are placed at the peak of the research arena for their underlying benefits as mentioned by multiple researches. Out of a number of vegetable oils, only a few are used commercially for biodiesel production. Due to various limitations of edible oil, non-edible oils are becoming a profitable choice. Till today, very little percentage of biodiesel is used successfully in engine. The research is still continuing for improving the biodiesel usage level. Recently, it is found that the blended biodiesel from more than one feedstock provides better performance in engine. This paper reviews the physicochemical properties of different biodiesel blends obtained from various feedstocks with a view to properly understand the fuel quality. Moreover, a short description of each feedstock is given along with graphical presentation of important properties for various blend percentages from BO to B100. Finally, mathematical model is formed for predicting various properties of biodiesel blend with the help of different research data by using polynomial curve fitting method. The results obtained from a number of literature based on this work shows that the heating value of biodiesel is about 11 lower than diesel except coconut (14.5 lower) whereas kinematic viscosity is in the range of 4-5.4 mm(2)/s. Flash point of all biodiesels are more than 150 degrees C, except neem and coconut. Cold flow properties of calophyllum, palm, jatropha, moringa are inferior to others. This would help to determine important properties of biodiesel blend for any percentage of biodiesel and to select the proper feedstock for better performance. (C) 2015 Elsevier Ltd. All rights reserved.